2018
DOI: 10.1007/s11886-018-0966-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Pulmonary Valve Replacement: Current State of Art

Abstract: Since its introduction in 2000, more than ten thousands tPVR procedures have been performed worldwide. Although the indications for tPVR have been adapted earlier from those accepted for surgical intervention, they remain incompletely defined. The new imaging modalities give better assessment of cardiac anatomy and function and determine candidacy for the procedure. The procedure has been shown to be feasible and safe when performed in patients who received pulmonary conduit and or bioprosthetic valves between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 75 publications
2
32
0
Order By: Relevance
“…Our observations confirm previous studies that showed a reduction of TR in even 65% of patients over 5 years of follow-up [13,14]. We agree with Alkashkari et al that these observations will lead to the extension of indications for TPVI [5].…”
Section: Early Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our observations confirm previous studies that showed a reduction of TR in even 65% of patients over 5 years of follow-up [13,14]. We agree with Alkashkari et al that these observations will lead to the extension of indications for TPVI [5].…”
Section: Early Resultssupporting
confidence: 93%
“…Procedural success was achieved in 93% with no mortality. In other studies, the procedural success rate was similar or slightly better (95%), but with mortality of 1.5 (0.8-2.6)% [4,5]. Freedom from reintervention, surgery, or endocarditis in our group was 99% in 1 year and 85.8% in mean 5.5 years of observation after TPVI.…”
Section: Discussionsupporting
confidence: 68%
“…1 The procedure is now widely accepted as an option for RVOT dysfunction. 2,3 The Sapien valve series (Edwards Lifesciences, Irvine, CA), including the second-generation Sapien XT valve and the third-generation Sapien 3 (S3) valve, was initially developed for transcatheter aortic valve implantation (TAVI) and are now also commonly used for TPVI.…”
Section: Introductionmentioning
confidence: 99%
“…Since Bonhoeffer et al demonstrated the first successful transcatheter pulmonary valve implantation (TPVI) for a patient with insufficiency of a right ventricular outflow tract (RVOT) conduit in 2001, the device technologies and delivery techniques have continually been refined to improve their performance 1 . The procedure is now widely accepted as an option for RVOT dysfunction 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…Transcatheter pulmonary valve replacement (TPVR) represents a valid option treatment for patients suffering from valvular heart diseases. 1 Current clinically approved heart valve substitutes for TPVR consist of glutaraldehyde-fixed animal-derived materials (e.g., bovine and porcine pericardium and porcine heart valves). 2 Owing to their animal origin, such substitutes are prone to progressive structural degradation and calcific degeneration, thus requiring multiple substitutive re-interventions, which are particularly critical for young patients.…”
Section: Introductionmentioning
confidence: 99%